2018
DOI: 10.1177/0002764218755835
|View full text |Cite
|
Sign up to set email alerts
|

Global Online Subculture Surrounding School Shootings

Abstract: This study is grounded in extensive online ethnographic fieldwork and interviews with 22 people who expressed a deep interest in school shootings. Such people form a global online subculture; they share common interests and find the same cultural objects important. Media accounts of school shootings have fueled this subculture; its members participate in the recreation and circulation of online media content and give new meanings to that content. We found that people deeply interested in school shootings do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
0
21
0
3
Order By: Relevance
“…First, some forms of (attempted) shootings traditionally thought of as (attempted) public mass murder are gaining much wider support online. This is true for school shootings [35], "targeted individuals" [36],…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, some forms of (attempted) shootings traditionally thought of as (attempted) public mass murder are gaining much wider support online. This is true for school shootings [35], "targeted individuals" [36],…”
Section: Discussionmentioning
confidence: 98%
“…First, some forms of (attempted) shootings traditionally thought of as (attempted) public mass murder are gaining much wider support online. This is true for school shootings [35], “targeted individuals” [36], Incels [37], and various forms of conspiracy theories that cross the Rubicon into inspiring political violence (e.g., QAnon [38]). As these locales grow, it will likely foster more leakage behaviors amongst the few who mobilize to violence.…”
Section: Discussionmentioning
confidence: 99%
“…Much like media coverage of movie stars and professional athletes creates fans of those celebrity types, media coverage of mass killers creates fans and followers as well. Raitanen and Oksanen (2018) found that these people are fascinated by previous attackers for a variety of reasons, including sexual attraction, deep sympathy, intense curiosity, or the desire to commit their own copycat attacks. Their obsessions are largely fed by media coverage of past perpetrators, which provides the names, photos, and life stories that they craft into objects for future worship and share online.…”
Section: The Consequences Of Media Coverage Of Mass Killingsmentioning
confidence: 99%
“…Research also has been conducted about the presence of school shooting fan communities online (Oksanen et al, 2014;Raitanen & Oksanen, 2018). These studies reveal that several groups, including fan girls, researchers, Columbine fans, and copycats find communities online.…”
Section: Gun Violence Conversations On Social Mediamentioning
confidence: 99%
“…These studies reveal that several groups, including fan girls, researchers, Columbine fans, and copycats find communities online. They also indicate that social media have the potential to function as powerful arenas for idea sharing and violence justification (Oksanen et al, 2014;Raitanen & Oksanen, 2018).…”
Section: Gun Violence Conversations On Social Mediamentioning
confidence: 99%